Patients with colorectal peritoneal metastases and high peritoneal cancer index may benefit from cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Issue 12 (December 2020) - Birgisson, Helgi; Enblad, Malin; Artursson, Sara; Ghanipour, Lana; Cashin, Peter; Graf, Wilhelm
Abstract: Background: Peritoneal cancer index (PCI) >20 is often seen as a contraindication for cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with peritoneal metastases (PM) from colorectal cancer. The aim of this study was to compare the overall survival in colorectal PM patients with PCI >20 and PCI ≤20 treated with CRS and HIPEC to those having open-close/debulking procedure only. Methods: All patients with colorectal PM and intention to treat with CRS and HIPEC in Uppsala Sweden 2004–2017 were included. Patients scheduled for CRS and HIPEC were divided into three groups, PCI >20, PCI ≤20, and those not operated with CRS and HIPEC stated as open-close including those treated with palliative debulking. Results: Of 201 operations, 112 (56%) resulted in CRS and HIPEC with PCI ≤20, 45 (22%) in CRS and HIPEC with PCI >20 and 44 (22%) resulted in open-close/debulking. Median survival for CRS and HIPEC and PCI >20 was 20 months (95%CI 14–27 months) with 7% surviving longer than 5 years (n = 3). For CRS and HIPEC and PCI ≤20 the median survival was 33 months (95%CI 30–39 months) with 23% (n = 26) surviving >5years. The median survival for open-close was 9 months (95%CI 4–10 months), no one survived >5years. Conclusion: Patients with PM from colorectal cancer and PCI >20 that were treated with CRS and HIPEC experience a one year longer and doubled overall survival compared with open-close/debulking patients. In addition to PCI, more factors should be taken into account when a decision about proceeding with CRS or not is taken. Highlights: Patients with peritoneal metastasis from colorectal cancer and peritoneal cancer index >20 that were treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy experience a doubled overall survival compared with open-close/debulking patients. In addition to peritoneal cancer index, more factors should be taken into account when a decision about proceeding with the cytoreductive surgery or not is taken.